VOC Sampler on a Drone Assisting in Tracing the Potential Sources by a Dispersion Model — Case Study of Industrial Emissions - Wen-Hsi Cheng; Ching-Ho Lin; Chung-Shin Yuan (Aerosol and Air Quality Research)
Abstract Volatile organic compound (VOC) related air pollution cause public concern and pose adverse effects on human health in the communities in most developed and developing countries. Our recent studies have applied a quadrotor drone (Mavic Pro, DJI) equipped with a micro needle trap sampler (NTS), and it could fast arrive at the polluted locations for immediately sampling and further tracking the suspended VOC sources. Notably, a remote-controlled telescoping sampling device was also equipped on the drone in order to extend the NTS outside the disturbed downward wind zone, which was resulted from the rotating propellers. Two plants which manufacture petrochemical products at an industrial complex in Kaohsiung City, southern Taiwan, were applied as the targets for VOCs sampling and further qualitative and quantitative analysis in the laboratory. Aromatic hydrocarbons, including toluene of 433 ppb, ethylbenzene and xylenes of 100–200 ppb and phenol of 111 ppb were identified. Additionally, an air mass backward trajectory model, FYTRAJ, was used to track the paths of VOC emitted from the potential sources and transported in the ambient air. According to the analyzed constituents of VOCs and the raw material data of the suspected plant, which was combined with the backward trajectory tracking simulation of VOC plumes, the NTS carried by a drone has been proven as a cost-effective air pollution monitoring apparatus for locating the VOC emission sources.